An admirable wife / Tengku Nurul Syahira Abdul Rasheed...[et al.] - Abdul Rasheed, Tengku Nurul Syahira; Sarizal, Farah Batrisyia; Adnan, Nur Atiqah Fatihah; Mamat, Anisa; Kamsani, Anis Nor Syuhada (Faculty of Communication & Media Studies, 2019)
Wife is a married woman, especially when considered in relation to her partner in marriage. This study is done in order to find the main criteria for men to choose a woman as their soul mate. The minimum sample size was determined through G⃰Power analysis. The study involved 851 respondents, selected through a purpose sampling technique involving three main ethnics in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables were measured through scales previously used by other researchers. SPSSS ver. 20 software was used in the analysis. Results of the SPSS indicated that for the main criteria for men to choose a woman as their soul mate are maturity (M=3.23) then virginity (M=3.10).